Correlation of body condition and occurrence of anoestrus in buffaloes - Daheriya, Santosh Kumar; Shivhare, Madhu; Shukla, Suresh Prasad; Nema, Sant Prasad (Buffalo Bulletin, 2023)
The present study was conducted on 30 buffaloes belonging to department of veterinary gynaecology and obstetrics and village around college of Veterinary Science and Animal Husbandry, Mhow (M.P.), buffalo were selected on the basis of history, which had not exhibited oestrus for 90 days or more postpartum, clinical examination of these buffaloes were made for general health and reproductive soundness, per rectally explored twice 10 days apart to confirm ovarian activity and genital status, the animals is awarded an appropriate body condition score 1 (very thin) to 5 (fat) on practice half score were used for animals whose condition score is intermediate. the experiment was done on 30 buffaloes divided into 6 groups, each group consist of 6 buffaloes. The body condition score on scale 1 (very thin) to 5 (fat) ranged between. Body condition score in anoestrus buffaloes was significantly lower than the normal cycling buffaloes. There is a positive relationship between body condition score and subsequent reproductive performance of the animals.